Association of TNF-related apoptosis inducing ligand receptor (TRAIL-R) gene polymorphisms in Iranian Azeri patients with multiple sclerosis - Amir Taghavi, Bita; Hashemi, Mehrdad; Niaei, Gholamreza; Rahmani, Seyed Ali (Archives of Advances in Biosciences, 2016)
Introduction: Multiple sclerosis (MS) is a chronic inflammatory demyelinating disorder of the central nervous system with various degrees of axonal damage. The TNF-related apoptosis inducing ligand receptor (TRAIL-R) might be playing an important role in the pathogenesis of MS. The objective of our study was to evaluate the association of two common polymorphisms is located in the TRAIL-R1 and TRAIL-R2 gene, in the pathogenesis of MS. Methods: We genotyped two single nucleotide polymorphisms in particular regions with single strand conformation polymorphism (SSCP) and Results obtained from the sequence of some samples, were analyzed using DNAMAN software. DNA was extracted from whole blood using the salting-out procedure. The distribution of genotype frequencies was analyzed using Pearson’s x2 test. Statistical significance was defined as p < 0.05. Results: No Significant differences in SNP rs4872077 were found between the PRMS and PPMS groups and No association was found between the genotype status of the rs1001793 and rs4872077 polymorphisms and the age at onset, disease duration, EDSS. Conclusion: Our study suggests no association between TRAILR polymorphisms and MS Disease. Nevertheless, this polymorphisms does not appear to be a severity marker of the disease, neither modifying the clinical progression of MS nor its therapeutic response.